The Subject of Girls’ Education in School Reforms from the National Education Commission to World War II - Dormus, Katarzyna (Biuletyn Historii Wychowania, 2018)
At the end of the 18th century and during the partitions, the education of young females constituted a separate educational track. At elementary level, young females had access to regular schools. At secondary level, private and monastic schools dominated. The government’s first interference with the education of young females was, perhaps, the attempt by the Commission of National Education to establish a permanent supervision of certain female schools (under legislation from 1775). The laws regarding education in each partition were not commensurate with the growing educational aspirations of women and the general socio-economic conditions. The Russian Partition was characterised by the dual existence of Polish private schools an governmental schools focused on the Russification of young Polish females. In Galicia, the most controversial issue was the creation of female secondary schools, the completion of which would enable a young woman to pursue university studies. Only during the Second Polish Republic did female education achieve equality before the law.